Antibacterial activity of Cordyline fruticosa leaf extracts and its endophytic fungi extracts - Elfita Elfita; MARDIYANTO; FITRYA; JUWITA EKA LARASATI; JULINAR; HARY WIDJAJANTI; MUHARNI (Society for Indonesian Biodiversity, 2019)
Abstract. Elfita, Mardiyanto, Fitrya, Larasati JE, Julinar, Widjajanti H, Muharni. 2019. Antibacterial activity of Cordyline fruticosa leaf extracts and its endophytic fungi extracts. Biodiversitas 20: 3804-3812. Endophytic fungi live by forming colonies in plant tissues without harming the host plant. Cordyline fruticose has been used as traditional medicine for the treatment of pathogenic bacterial infections; therefore, its endophytic fungi are expected to have similar activity. In this study, C. fruticosa leaves were extracted with gradient solvents and evaluated for their antibacterial activity using the Kirby–Bauer method against Gram-negative (Salmonella typhi, Escherichia coli) and Gram-positive (Staphylococcus aureus, Bacillus subtilis) bacteria. The extracts of endophytic fungi from C. fruticosa leaves were evaluated for their antibacterial activity, as well. The endophytic fungus with good antibacterial activity was identified by molecular and phylogenetic methods. Chemical compounds from endophytic fungus DB1 were isolated by chromatography and subsequently determined by spectroscopy. The methanol extract of C. fruticosa leaves showed strong antibacterial activity equivalent to the endophytic fungus (DB1). Molecular identification and analysis through the phylogenetic tree showed that the DB1 fungus has a high level of similarity to Neurospora tetrasperma strain APBSDSF108. The antibacterial compounds (compound 1 and 2) isolated from the endophytic fungus DB1 were identified as 4-hydroxy-5-phenylpenta-1,3-dien-1-yl acetate and ergosterol, respectively.